Physical properties of coir and pineapple leaf fibre reinforced polylactic acid hybrid composites - Siakeng, R.; Jawaid, Mohammad; Ariffin, Hidayah; Salit, Mohd Sapuan (IOP Publishing, 2018)
This study examined the physical behaviour of Coir fibres (CF)/Pineapple leaf fibres (PALF)/Poly lactic acid (PLA) composites. In this research, coir and PALF reinforced PLA hybrid composites were fabricated by hand lay-up process and hot press. The aim of this work is to do comparative study on density, water absorption (WA) and thickness swelling (TS) of untreated CF/PALF reinforced PLA composites and hybrid composites. The effect of different fibre ratios in hybridization on density, WA and TS of CF/PALF hybrid composites were also analyzed and C7P3 showed highest density while P30 had lowest. The results indicated that the density varies on different fibre ratio. WA and TS of CF/PALF composites and hybrid composites vary with fibres ratio and soaking duration. WA and TS of untreated CF/PALF hybrid composites were increased by increasing coir fibre ratio so, C30 showed highest WA and TS whereas P30 and C1P1 showed least WA and TS respectively apart from neat PLA.